Research on the Mechanism of the Role of Innovation-Influencing Factors on the Performance of Construction Projects - Shiming Wang; Caiyun Li (Advances in Civil Engineering)
At present, innovation has gradually become an inevitable trend of the digital transformation and competitive advantage of enterprises in the construction industry. In this paper, the structural equation model is constructed from four aspects of innovation-influencing factors, such as hindering, driving, enabling, and investing, as well as project and enterprise performance. The participants of engineering construction projects from several regions in China have been investigated. Factor analysis and structural equation model analysis have been carried out on the collected data using SPSS and AMOS software. Both drive factors and enabling factorss can play an important role in promoting innovation input. As an intermediary variable, innovation input can directly stimulate project and enterprise performance, and the improvement of enterprise performance is also positively dependent on project performance.